Implementation of the State Civil Apparatus Code of Ethics Policy at the National Unity and Politics Agency of Tanah Datar Regency - Suci Intan Rahmadani; Rahmadani Yusran (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The implementation of the Civil Servant (ASN) code of ethics policy is an important instrument in building apparatus compliance and strengthening governance with integrity. Although the regulatory framework regarding the ASN code of ethics is available, the effectiveness of its implementation still faces various challenges in the practice of regional government administration. This study aims to analyze the implementation of the ASN code of ethics policy in building apparatus compliance at the National Unity and Politics Agency of Tanah Datar Regency. The study used a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The research analysis uses the policy implementation perspective of George C. Edwards III which emphasizes the dimensions of communication, resources, disposition, and bureaucratic structure. The results show that apparatus compliance is built through three interrelated implementation mechanisms: policy communication through the socialization of the code of ethics, apparatus development that strengthens commitment to ethical values, and monitoring and evaluation supported by the bureaucratic structure and the use of digital technology. Policy implementation is not only oriented toward enforcing regulations, but also fostering an organizational culture that promotes integrity, professionalism, discipline, and accountability among officials. This research confirms that the effectiveness of code of ethics policy implementation is determined more by integrated communication, coaching, and oversight than by the mere existence of regulations as normative instruments.